A Computational Analysis of Four RETNSNPs in Iraqi Women with Breast Cancer: A Cross-Sectional Study - Sahan, Khadija A.; Sahan, Zahraa A.; Turki , Thualfiqar Gh. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Breast cancer is a leading malignancy in women, shaped by genetic and environmental factors. Resistin, a potential chemotherapy target, may contribute to chemoresistance when mutated. This study applies computational methods to analyze how single-nucleotide polymorphisms alter resistin’s structure and function, potentially reducing its chemotherapy sensitivity.Methods:  A total of 105 fresh blood samples were collected from patients recruited from the Oncology Teaching Hospital, Medical City, Baghdad, Iraq. between March-2020 and September-2023. Samples were classified into 3 groups of 35 samples each: control, benign and patients. DNA extraction, PCR, Sanger sequencing and computational approaches were used to analyze four resistins' polymorphisms, namely rs1862513, rs3219175, rs34788323, and rs3745367. Functional impacts were predicted using HaploReg (regulatory effects), RegulomeDB (regulatory annotations), PolyPhen-2 (pathogenicity), ProtParam (protein stability), and SWISS-MODEL (3d structural modelling).  Data entry, descriptive statistics, and statistical analyses were performed using IBM SPSS Statistics version 20. The chi-squared test was applied, and a p-value